Efeitos do jejum agudo ou jejum intermitente na evolução da peritonite bacteriana induzida por ligadura e punção do ceco ou por injeção intra-peritoneal de suspensão fecal em camundongos - Bermudes, Fernando Antonio Martins (2007)
Intermittent fasting is frequent in medical practice and this condition has been studied as a therapeutic intervention for some diseases. Increased life span and resistance to stress is observed in rodents submitted to intermittent fasting. However there is not much information on the evolution of infections in animals submitted to these diet manipulations. To study the evolution of fecal peritonitis in mice after 72 h fasting or after different time of intermittent fasting. After 72 h of fasting mice were submitted to cecal ligature and puncture or to an intraperitoneal injection of feces (1:6 or 1:9, weight/volume dilutions). Mice submitted to intermittent fasting, three days for two weeks or the day after the other day, during four months, received intraperitoneal injection of feces with the same dilutions. Mortality was evaluated up to 14 days, when the animals were killed to quantify the intraperitonel abscesses. The abscesses were classified with the values one, two or three according they were respectively up two, between two and five or higher than five millimeters in diameter. For each animal a score was obtained by the sum of values originated from the product of the number attributed to the abscesses versus the number of each abscess type. Control mice, paired by gender and age, were submitted to the same procedures. In mice submitted to 72 h fasting or intermittent fasting the signs of septic shock appeared earlier and were more severe, with higher mortality up to 24 h, although the global mortality evaluated by Kaplan-Meyer method was not significant after two weeks. Among the survivors the score of abscesses were significantly lower in mice submitted to fasting, mainly in groups treated with feces 1:9 dilution, in which occurred less mortality. Results demonstrate that acute or intermittent fasting increases the susceptibility to endotoxic shock and induces increased resistance to bacteria, demonstrated by reduction in number and volume of abscesses.